STRATEGI PERSONAL BRANDING SEBAGAI PENDAKWAH DIGITAL PADA AKUN INSTAGRAM @ALFATAHAR_ - Rahmatika; Okditazeini, Vannyora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research is motivated by the rapid development of the digital world which also supports the role of da'wah on social media. The Instagram platform is one of the favorite platforms to convey da'wah online/digital-based. This digital dawah is one of the da'wah models that is widely used by the millennial generation because its teaching through the media and this da'wah model can be accessed anytime and anywhere. The purpose of this study is to analyze personal branding strategies as digital preachers on @alfatahar_ Instagram account. This study uses a descriptive qualitative method using the Miles & Huberman data collection technique. Data was collected from @alfatahar_ account uploads using purposive sampling techniques according to certain criteria, and data was taken from interviews with Sahar Alfatahar, the owner of the @alfatahar_ Instagram account. The results of the study show that the personal branding strategy that Sahar applied to her Instagram account is @alfatahar_ very effective in shaping her image as a digital preacher. Based on the analysis of the concept of forming personal branding according to Peter Montoya, it was found that almost all of its elements are; specialization, leadership, personality, distinctiveness, visibility, unity, persistence and goodwill, are applied by @alfatahar_ both in their daily lives and in the activities and content they upload on social media, especially Instagram. This can be seen from the consistency of the content, the distinctive communication style, the professional impression displayed, and the high level of audience engagement.